2003
DOI: 10.1001/archpsyc.60.11.1090
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Hyperintensity Progression and Late-Life Depression Outcomes

Abstract: Greater progression of WMH volume is associated with poor outcomes in geriatric depression. Future work is needed to develop means of slowing the rate of WMH progression and to determine whether this will lead to improved depression outcomes in elderly persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
151
4
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 212 publications
(166 citation statements)
references
References 62 publications
8
151
4
2
Order By: Relevance
“…Individuals who demonstrate a lack of persistence in a testing situation may be more likely to have problems with treatment adherence and other functional abilities. Like the task impersistence reported in the current study, poor treatment response and functional performance deficits have been found to be associated with white matter lesions at least partly involving the frontal lobes (Steffens et al, 2002a;Taylor et al, 2003). With additional research to clarify the construct, it is possible that task impersistence may be considered a marker for underlying prefrontal pathology and a higher risk of adverse clinical outcomes.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Individuals who demonstrate a lack of persistence in a testing situation may be more likely to have problems with treatment adherence and other functional abilities. Like the task impersistence reported in the current study, poor treatment response and functional performance deficits have been found to be associated with white matter lesions at least partly involving the frontal lobes (Steffens et al, 2002a;Taylor et al, 2003). With additional research to clarify the construct, it is possible that task impersistence may be considered a marker for underlying prefrontal pathology and a higher risk of adverse clinical outcomes.…”
Section: Discussionsupporting
confidence: 58%
“…Multiple areas of the frontostriatal pathway are involved in the process of planning, initiating, and maintaining complex behavioral responses, including orbitofrontal cortex, dorsolateral prefrontal cortex, and anterior cingulate (Rogers et al, 1998). White matter lesions in these broader brain regions are more prominent in depressed older adults relative to nondepressed elders (Taylor et al, 2005), and like initiation deficits, are associated with greater risk for adverse outcomes in depression, such as poor treatment response (Alexopoulos et al, 2002a;Taylor et al, 2003) and functional impairment (Steffens et al, 2002a). Identifying neuropsychological performances that are sensitive to prefrontal vascular pathology would be useful for characterizing individuals with this form of late-life depression.…”
Section: Introductionmentioning
confidence: 99%
“…The inability to demonstrate a statistically significant difference was likely due to a relatively short follow-up period and a sample size insufficient to detect a difference over the study period; however, the change we report is comparable to that found in other longitudinal studies investigating either total (Taylor et al, 2003a) or deep white matter lesion volume (Cook et al, 2004). Other studies have demonstrated that WMLs do increase in severity and volume over time, and that greater change is associated with depression outcomes (Nebes et al, 2002;Taylor et al, 2003c).…”
Section: Discussioncontrasting
confidence: 56%
“…White and gray matter hyperintense lesions are more severe in older depressed subjects than nondepressed subjects (Krishnan et al, 1988;Dolan et al, 1990;Fujikawa et al, 1993;Krishnan, 1993;Greenwald et al, 1996;Steffens et al, 1999;Kumar et al, 2000;Tupler et al, 2002;Taylor et al, 2005), and are more severe in late-onset than early-onset elderly depressed subjects (Figiel et al, 1991;Hickie et al, 1995;Salloway et al, 1996;Krishnan et al, 1997;Lavretsky et al, 1998;de Groot et al, 2000;Tupler et al, 2002). Increases in WML severity over time are additionally associated with new onset of depression (Lavretsky et al, 1999;Nebes et al, 2002) and poorer outcomes to antidepressant therapy (Simpson et al, 1997;O'Brien et al, 1998;Taylor et al, 2003c), although some have not found a relationship between WML severity and treatment outcomes (Salloway et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…4,5 In clinical samples, progression of MRI white matter lesions is related to lack of response to antidepressants or recurrence of depression. 6 However, in these samples nearly all subjects received pharmacological treatment. The effect of antidepressant medications on progression of brain vascular disease defined by MRI is unclear.…”
mentioning
confidence: 99%